FRACTIONAL ORDER PROPORTIONAL-INTEGRAL-DIFFERENTIAL BASED CONTROLLER DESIGN FOR DC MOTOR SPEED CONTROL - Sanket Hari Nankar; Prof. Ashok M. Jain (International Journal of Innovations in Engineering Research and Technology, 2021)
Fractional order calculus has become a growing area in the field of control theory. This phenomenon allows us to describe and model a real object more accurately than the conventional “integer” methods. One of the important applications of fractional calculus is fractional order PID controller which has gained a prominent recognition in various industrial applications. These fractional order PID controllers are more advanced than the traditional PID controllers and they also give stringent performances. This paper deals with the design of fractional order proportional–integral–differential (PID) controller. It also gives the control aspect of fractional order PID controller in speed control of DC motor. A comparative study of classical PID controller & fractional order PID controller has been performed.